2008
DOI: 10.1002/mds.21667
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in Parkinson's disease: The relative importance of the symptoms

Abstract: A body of literature now exists, which demonstrates that idiopathic Parkinson's disease (PD) has a major negative impact on quality of life (QoL), and that depression and cognitive impairment are among the main predictors of poor QoL in this disorder. Relatively little work has been done to assess the differential contribution of the specific symptoms of PD to QoL, which was the aim of this study. One hundred thirty patients with PD completed a booklet of questionnaires, which included the PDQ39 as a disease-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

28
283
5
16

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 450 publications
(332 citation statements)
references
References 37 publications
28
283
5
16
Order By: Relevance
“…Falls can have devastating consequences including restriction or avoidance of physical activities [2,3] and reduced health-related quality of life [4].…”
Section: Introductionmentioning
confidence: 99%
“…Falls can have devastating consequences including restriction or avoidance of physical activities [2,3] and reduced health-related quality of life [4].…”
Section: Introductionmentioning
confidence: 99%
“…These symptoms can be broadly classified into neuropsychiatric problems (including disturbances in cognition and mood), sleep disturbances and autonomic symptoms. These non-motor symptoms commonly dominate the clinical picture in severe PD and, as such, have a significant impact on quality of life and disability (Rahman et al, 2008). The pathophysiology of these symptoms remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] In PD patients, disability can result from distinct features such as motor impairment, non-motor complications, 4,8 and treatment side effects. Studies have shown that PD-related motor symptoms, [9][10][11][12][13] affective disorder, [13][14][15][16][17] and cognitive dysfunction 14 can be determinants of quality of life. According to the World Health Organization (WHO), quality of life (QOL) is "individuals' perception of their position in life in the context of the culture and value systems in which they live and in relation to their goals, expectations, standards and concerns".…”
Section: Introductionmentioning
confidence: 99%